Self‐Reported Driving Difficulty in Veterans With Traumatic Brain Injury: Its Central Role in Psychological Well‐Being. Issue 9 (4th February 2017) - Winter, Laraine; Moriarty, Helene J.; Short, Thomas H.
Abstract : Background: The ability to drive is a core function supporting independent living. Traumatic brain injury (TBI) may impair driving capacity in numerous ways. Previous research has documented that individuals with TBI have more driving‐related problems than other people and has identified predictors of driving status or capacity, mostly among civilians; however, no research has examined the implications of driving limitations for the well‐being of individuals with TBI. Objective: To examine the association between self‐reported difficulty in driving with important domains of psychological well‐being in veterans with TBI, with adjustment for posttraumatic stress disorder (PTSD) and years since most recent TBI. Design: Cross‐sectional. Setting: Veterans' homes. Participants: A total of 61 veterans of the Global Wars on Terrorism diagnosed with TBI, all outpatients at a Veterans Affairs medical center rehabilitation service. Methods: Home interviews as a baseline assessment for a larger randomized controlled trial. Main Outcome Measures: Community reintegration (extent of social participation), depressive symptomatology, and role limitations due to physical health problems and those due to emotional problems. Self‐rated competence in driving was the predictor, and sociodemographic characteristics, diagnosis of PTSD, severity of TBI, and time since most recent TBI were covariates. Results: Self‐rated driving difficulty was associated with decreased community reintegration (β = .280, P =.028), greater depressive symptomatology (β = −.402, P < .001), and greater role limitations due to physical problems (β = −.312, P =.011) and to emotional problems (β = −.324, P = .006), after we adjusted for PTSD and other variables. Discussion: The self‐reported ability to drive seems to be central to psychological well‐being in veterans with TBI, showing clear associations with depression, community reintegration, and health‐related role limitations. These associations cannot be attributed to comorbid PTSD. Conclusion: Rehabilitation specialists should view driving difficulty as a risk factor for poor psychosocial outcomes in veterans with TBI and seek ways to compensate for the veteran's loss of driving if it is no longer advisable. Level of Evidence: II